The Human Body: The heart: The living pump - Davis, Goode; Park, Edwards; Pinchot Roy (New York : Torstar Books, 1984)
La serie The Human Body cuenta con cuatro ejemplares en donde cada uno nos enseña de una manera diferente cada parte del cuerpo
1. From logic to lightt 2. The Pears-Shaped heart 3. The coronary puzzle 4. A surging pump 5. Disorders of the heart 6. Modern Miracles
Incluye índice
Keywords: EL CUERPO HUMANO; CORAZÓN; OLFATO; CORAZÓN -- ENFERMEDADES